Jejunogastric intussusception after pancreaticoduodenectomy: a case report - Konosuke Yogo; Masanori Sando; Ryutaro Kobayashi; Genta Yano; Noriaki Ohara; Kiyotaka Kawai; Kenji Takagi; Satoru Kawai; Satoaki Kamiya (Surgical Case Reports)
Abstract Background Jejunogastric intussusception (JGI) is a rare, but potentially fatal complication that can occur following gastric surgery, and the reported incidence of JGI is as low as 0.1%. Early diagnosis and treatment are critical for JGI to prevent major complications such as bowel necrosis and death. Although emergency surgery is the standard treatment, endoscopic reduction has also been reported to be effective in JGI patients without bowel necrosis. Several early recurrent cases treated with surgical or endoscopic reduction have been reported. We report an extremely rare case of JGI after pancreaticoduodenectomy (PD) using Child’s procedure that was successfully treated with surgical reduction and fixation. Case presentation An 81-year-old man who had undergone PD using Child’s procedure 3 years ago presented to our hospital with epigastric pain and nausea. His vital signs were stable, and abdominal examination revealed mild tenderness with a palpable mass in the mid-epigastrium. Abdominal computed tomography (CT) and gastroscopy revealed a JGI of the efferent loop, and exploratory laparotomy was immediately performed. During the operation, the efferent loop showed no adhesions and was intussuscepted through the gastrojejunostomy into the gastric lumen. An incision in the anterior wall of the stomach revealed no evidence of ischemia of the intussusceptum. The efferent loop was reduced using Hutchinson’s maneuver and fixed to the afferent loop to prevent a recurrence. The postoperative course was uneventful, and there was no sign of recurrence 12 months postoperatively. Conclusions JGI after PD is an extremely rare, but has severe complications. Surgery might be the optimal treatment for JGI in terms of preventing recurrence, even in cases without bowel necrosis.